Les variations récentes (1975-2000) de l’englacement dans le Massif de l’Aconcagua (Mendoza, Argentine) - Etienne Cossart; Julie Le Gall (EchoGéo)
Mendoza area is highly vulnerable to the global warming. The glaciers of the Aconcagua massif are currently shrinking, this trend of retreat began at the end of the Little Ice Age. The disappearance of glaciers may modify hydrological regimes. The discharge is currently at maximum during summer (related to glacier melt), but the peak discharge may occur during spring (related to snow melt) in the next future. In this paper we synthesize the recent variations of the glaciers and propose a pattern of future variations.